Accurate stereo matching using pixel normalized cross correlation in time domain. (1st January 2016) - Lelas, Marko; Pribanić, Tomislav
Abstract : This paper proposes a novel method for stereo matching which is based on combination of active and passive stereo 3D reconstruction approaches. A laser line is used to scan the reconstructed scene and a stereo camera pair is used for the image acquisition. Each image pixel is scanned at a specific scan time so that the intensity time patterns of the correspondent pixels are highly correlated. This yield in highly confident and accurate disparity map calculation and also allows the reconstruction of poorly textured as well as the extremely textured surface which are very hard to deal with using the conventional passive stereo approaches. The occluded regions are also detected successfully. This method is not computationally intensive and can be used for turning the smartphone into the practical 3D scanner as presented in this work.